Role of Cytokines and Toll-Like Receptors in the Immunopathogenesis of Guillain-Barré Syndrome - Kishan Kumar Nyati; Kashi Nath Prasad (Mediators of Inflammation)
Guillain-Barré syndrome (GBS) is an autoimmune disease of the peripheral nervous system, mostly triggered by an aberrant immune response to an infectious pathogen. Although several infections have been implicated in the pathogenesis of GBS, not all such infected individuals develop this disease. Moreover, infection with a single agent might also lead to different subtypes of GBS emphasizing the role of host factors in the development of GBS. The host factors regulate a broad range of inflammatory processes that are involved in the pathogenesis of autoimmune diseases including GBS. Evidences suggest that systemically and locally released cytokines and their involvement in immune-mediated demyelination and axonal damage of peripheral nerves are important in the pathogenesis of GBS. Toll-like receptors (TLRs) link innate and adaptive immunity through transcription of several proinflammatory cytokines. TLR genes may increase susceptibility to microbial infections; an attenuated immune response towards antigen and downregulation of cytokines occurs due to mutation in the gene. Herein, we discuss the crucial role of host factors such as cytokines and TLRs that activate the immune response and are involved in the pathogenesis of the disease.